The effect of risk of contracting and fear of COVID-19 on burnout and job satisfaction in Polish teachers - Joanna Dymecka; Rafał Gerymski; Radoslaw B. Walczak; Aleksandra Jania (Current Issues in Personality Psychology)
Background Fear of COVID-19 and its related complications can negatively affect well-being and contribute to less effective daily and professional functioning. Based on Maslach’s burnout concept, this study aimed to verify the relationship between risk of contracting and fear of COVID-19, occupational burnout and job satisfaction in Polish teachers during the second wave of the COVID-19 pandemic.